FACTORS AFFECTING ON IMPLEMENTATION OF NURSING PROCESS - WARIS, M; JAVED, R; AMIR, Z; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
The nursing process is a critical framework for providing high-quality, patient-centered care, consisting of five essential steps: assessment, diagnosis, planning, implementation, and evaluation. In Pakistan, the successful implementation of the nursing process is hindered by various barriers, including inadequate training, time constraints, and insufficient resources. Understanding the factors that affect its implementation is crucial for improving care delivery in healthcare settings. Objective: This study aimed to evaluate the factors affecting the implementation of nursing care plans among nurses at Sir Ganga Ram Hospital, Lahore, Pakistan. The study explores the relationship between nurses’ demographic characteristics, such as education, experience, and job nature, and their ability to effectively implement the nursing care plan. Methods: A cross-sectional quantitative descriptive design was employed, involving a sample of 200 nurses. Data were collected using a structured questionnaire adapted from Brookings (2004), which assessed factors related to the implementation of the nursing process, including Assessment and Diagnosis, Planning, Implementation, and Evaluation. Descriptive and inferential statistics were used to analyze the data. Results: The study found that nurses performed best in the Implementation phase (mean = 40.36), with lower scores in the Assessment and Diagnosis phase (mean the Implementation = 23.09). Educational qualifications and experience positively influenced the implementation of nursing care plans. The reliability and validity of the measurement tools were confirmed with satisfactory results. Conclusion: The findings underscore the importance of addressing gaps in the Assessment and Diagnosis phase to enhance the overall effectiveness of the nursing care plan. Continuous education and targeted interventions are recommended to improve the implementation of nursing care plans, ultimately contributing to better patient care outcomes in Pakistan.